2011
DOI: 10.1080/03079457.2010.540002
|View full text |Cite
|
Sign up to set email alerts
|

Variation in viral shedding patterns between different wild bird species infected experimentally with low-pathogenicity avian influenza viruses that originated from wild birds

Abstract: The prevalence of infection with avian influenza (AI) virus varies significantly between taxonomic Orders and even between species within the same Order. The current understanding of AI infection and virus shedding parameters in wild birds is limited and largely based on trials conducted in mallards (Anas platyrhynchos). The objective of the present study was to provide experimental data to examine species-related differences in susceptibility and viral shedding associated with wild bird-origin low-pathogenici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
54
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 71 publications
(58 citation statements)
references
References 35 publications
(50 reference statements)
4
54
0
Order By: Relevance
“…As a comparison, antibody prevalence in mallards (Anas platyrhynchos) and Canada geese (Branta canadensis) sampled during these same time periods can exceed 50% and 20%, respectively (Brown et al, 2010;Kistler et al, 2012). Although, the duration of the detectable IAV antibody response is not well defined for wood ducks, and may partially explain the low prevalence, antibodies to IAV nucleoprotein have been detected for more than 1 year in naturally exposed mallards (Fereidouni et al, 2010) and for 21 days in experimentally infected wood ducks and mallards (Costa et al, 2011). These results suggest that wood ducks are probably spillover hosts of IAVs, and it is possible that previously reported isolations of IAV from this species reflect such spillover Hinshaw et al, 1985;Wilcox et al, 2011).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…As a comparison, antibody prevalence in mallards (Anas platyrhynchos) and Canada geese (Branta canadensis) sampled during these same time periods can exceed 50% and 20%, respectively (Brown et al, 2010;Kistler et al, 2012). Although, the duration of the detectable IAV antibody response is not well defined for wood ducks, and may partially explain the low prevalence, antibodies to IAV nucleoprotein have been detected for more than 1 year in naturally exposed mallards (Fereidouni et al, 2010) and for 21 days in experimentally infected wood ducks and mallards (Costa et al, 2011). These results suggest that wood ducks are probably spillover hosts of IAVs, and it is possible that previously reported isolations of IAV from this species reflect such spillover Hinshaw et al, 1985;Wilcox et al, 2011).…”
Section: Discussionmentioning
confidence: 96%
“…Finally, most of these studies only tested cloacal swabs. However, it has since been reported that wood ducks predominantly shed IAVs via the oropharyngeal route (Costa et al, 2011), indicating that the role wood ducks play in the epidemiology of infections with IAVs may be spatially dependent or poorly defined due to sampling focused on cloacal swabs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The absence of variation between virus genotypes contrasts with host-related effects that can significantly affect the outcome of virus shedding. Recent studies have for instance highlighted the effect of bird host species [40], age [38,41], body condition [42] and preexposure to other IAV [43,44], in the CL shedding duration and viral load. Such host-related variations may have direct implications in the transmission dynamics of IAV in wild duck populations.…”
Section: Discussionmentioning
confidence: 99%
“…In ducks, the naturally occurring endemic LPAI viruses are typically enterotropic and are shed primarily through feces (62)(63)(64). a Two-week-old mallard ducks were i.n.…”
Section: Discussionmentioning
confidence: 99%